SARS‐CoV‐2 in the semen: Where does it come from?. (28th July 2020) - Massarotti, Claudia; Garolla, Andrea; Maccarini, Elena; Scaruffi, Paola; Stigliani, Sara; Anserini, Paola; Foresta, Carlo
Abstract: Background: The recent report of SARS‐CoV‐2 presence in semen samples of six patients, including two subjects who were recovering from the clinical disease, re‐opened the discussion on possible male genital tract infection, virus shedding in semen, sexual transmission and safety of fertility treatments during the pandemic period. Objectives: To explore current data and hypothesis on the possible sites of SARS‐CoV‐2 infection in the male reproduction system. Materials and methods: We reviewed the current literature to describe: a) the evidences on angiotensin‐converting enzyme 2 (AC2E) and transmembrane serine protease 2 (TMPRSS2) expression in the testes, accessory glands (including prostate) and the urinary tract; b) other coronaviruses' (SARS and MERS) ability to infect these sites. Results: The co‐expression of both ACE2 and TMPRSS2 genes was reported in spermatogonial stem cells, elongated spermatids, in at least a small percentage of prostate hillock cells and in renal tubular cells. Testicular damage was described in autopsies of SARS patients, without evidence of the virus in the specimens. Prostate is a known infection site for MERS‐CoV. SARS‐CoV‐2 was detected in urines. Discussion: There are still al lot of open questions on the effects of SARS‐CoV‐2 infection on the male reproductive tract. The presence of receptors is not a proof that the testis provides a site for viral infection and it is still unknown if SARS‐CoV‐2 is capable to pass the blood‐testis barrier. The possibility of a prostate involvement has not been investigated yet: we have no data, but theoretically it cannot be excluded. Moreover, the RNA detected in semen could have been just a residual of urinary shedding. Conclusion: Opening our prospective beyond the testis could be the key to better understand the possibility of a semen‐related viral transmission as well as COVID19 short and long‐term effects on male reproductive function.